On Tax Domicile in Tax Matters and the Condition of Not Been and Not Found - Robles Moreno, Carmen del Pilar (2014)
There are many kinds of legal addresses in the private sphere of a person, having different legal effects and treatments. In that line, the present paper will analyze the concept of tax address. For that purpose, first the concept of address will be introduced, then it’ll focus on tax address, to finally see the treatment of the address in the Tax Code. To finish, both Not Found and Not Been Adress will be analyzed, and so the tax consequences of each one.